Analysis of Preferable Occupation between Merchant and Islamic Bank Clerk in Bank Syariah Mandiri (BSM) Based on a Hadith about Riba - An'im Kafabih; Asfi Manzilati (Ekonomi Syariah IAIN Kudus, 2018)
This paper investigates the relationship between occupation to interest rate between Islamic bank clerk and merchant who export or import goods. As Prophet Muhammad ever said that at the end people still eat the “the dust of riba” event they want to avoid it, this implies that what people’s occupation will also be affected by the rate of interest rate. Introducing two model that represent the relationship between two occupation, merchant and Islamic bank clerks, and using ordinary regression, this study finds that statistically, as people want to be a merchant, they will gain much benefit when the rate of interest raise, however, when people prefer to become Islamic bank clerk (especially in BSM as case study), their income will harm as the rate of interest increase. In addition, when the interest rate rise, the benefit which is gained by merchant much greater than the loss of Islamic bank profit (BSM) because of the higher coefficient value of merchant rather than Islamic bank profit (BSM).